2021
DOI: 10.1111/gcb.15779
|View full text |Cite
|
Sign up to set email alerts
|

Conservation with elevated elephant densities sequesters carbon in soils despite losses of woody biomass

Abstract: Nature conservation and restoration in terrestrial ecosystems is often focused on increasing the numbers of megafauna, expecting them to have positive impacts on ecological self‐regulation processes and biodiversity. In sub‐Saharan Africa, conservation efforts also aspire to protect and enhance biodiversity with particular focus on elephants. However, elephant browsing carries the risk of woody biomass losses. In this context, little is known about how increasing elephant numbers affects carbon stocks in soils… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 91 publications
0
7
0
Order By: Relevance
“…A recent perspective highlights the importance of quantifying a diversity of carbon pools to better understand how herbivory impacts long‐term carbon storage (Kristensen et al 2022). As an example, Sandhage‐Hofmann et al (2021) demonstrated that elephants were able to compensate for most above ground carbon losses by increasing carbon stocks below ground. This is important, because it shows that research focusing solely on the above ground impacts may under or over‐estimate herbivore impacts on overall ecosystem carbon storage (Sandhage‐Hofman et al 2021, Kristensen et al 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent perspective highlights the importance of quantifying a diversity of carbon pools to better understand how herbivory impacts long‐term carbon storage (Kristensen et al 2022). As an example, Sandhage‐Hofmann et al (2021) demonstrated that elephants were able to compensate for most above ground carbon losses by increasing carbon stocks below ground. This is important, because it shows that research focusing solely on the above ground impacts may under or over‐estimate herbivore impacts on overall ecosystem carbon storage (Sandhage‐Hofman et al 2021, Kristensen et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…As an example, Sandhage‐Hofmann et al (2021) demonstrated that elephants were able to compensate for most above ground carbon losses by increasing carbon stocks below ground. This is important, because it shows that research focusing solely on the above ground impacts may under or over‐estimate herbivore impacts on overall ecosystem carbon storage (Sandhage‐Hofman et al 2021, Kristensen et al 2022). Moreover, studies are beginning to demonstrate that a focus on total SOC stocks alone fails to consider the effects of long‐term carbon storage, which also leads to under‐ or overestimation of climate change mitigation potential (Lehmann and Kleber 2015, Lehmann et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, browsers such as giraffes and dik‐diks play an important role in suppressing shrub encroachment and maintaining open grasslands, with benefits for wild and domestic grazers alike (Augustine et al, 2011). The presence of elephants in the conservancies is also crucial for maintaining ecosystem functions due to their positive effects on soil carbon and nitrogen pools, which can potentially reverse savanna degradation (Sandhage‐Hofmann et al, 2021; Sitters et al, 2020). Thus, a diverse assemblage of wild herbivores is an integral part of African rangeland conservation and restoration.…”
Section: Discussionmentioning
confidence: 99%
“…Sampling was stratified into two vegetation types (savanna and woodland) and three disturbance classes with low, medium, and high elephant densities; see Sandhage-Hofmann et al. (2021) [2] for details on this study design. Sites with ‘medium’ and ‘high’ elephant densities were located in the national parks Mudumu and Bwabwata, and least-disturbed sites with ‘low’ elephant densities were located in the respective adjacent communal conservancies Wuparo and Mashi.…”
Section: Methodsmentioning
confidence: 99%